Post-operative complications after cataract surgery with pseudophakos implantation at Dr Sardjito hospital - Suhardjo, Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Principally, complications of post operative cataract surgery with pseudophakos implantation cover those complications due to the operation, and those due to the existence of pseudophakos within the eye ball. In Dr. Sardjito hospital, this operation has been done since 1988. There are many kinds of complication of this operation. This retrospective study is limited to those complications in the form of anterior uveitis, endophthalmitis, secondary glaucoma, and endothelial decompensation which occurred within 1992-1994 period.A study has been performed on 405 cases, consisting of 397 cases with posterior chamber pseudophakos implantation and 8 cases with posterior chamber pseudophakos implantation. In the same period, a study on 432 cases with extra capsular cataract extraction without pseudophakos implantation was performed. The complication in the group with pseudophakos implantation were: anterior uveitis (2.96%), secondary glaucoma (1,48%), endhopthalmitis (0,99%), endothelial decompensation (0.74%) and other complications such as iris prolapse and subluxation of pseudophakos. The complication in the group without pseudophakos implantation were anterior uveitis (0.23%), endothelial decompensation (0.23%), and prolapse of iris 0.46%. In this study, the complication in the form of endophthalmitis occurred 1 week after surgery in 3 cases, and 2 weeks after surgery in one case. One case was caused by fungi infection. The complication in the form of secondary glaucoma mostly related with the occurence of post anterior uveitis surgery. The anterior uveitis in post cataract surgery with pseudophakos implantation was considered to be related with the kind of lens implanted.Key words : post operative complications -- cataract surgery -- pseudophakos implantation -- anterior uveitis -- kind bf lens implanted